Performance analysis of the teams that remained in the top-tier division of the Spanish LaLiga during eight consecutive seasons - Errekagorri, I.; López-Del Campo, R.; Resta, R.; Castellano, J. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2026)
The present study aimed to analyse the performance of 2212 collective observations of the eight teams that remained in the Spanish men`s top professional football division (Spanish LaLiga) for eight consecutive seasons (from 2011-2012 to 2018-2019), intending to understand the reference values of these teams. The variables recorded were passes, successful passes, crosses, shots, goals, corners, fouls, width, length, height, distance from the goalkeeper to the nearest defender (GkDef) and total distance covered (TD). A linear mixed model was performed for each dependent variable (p < 0.05). The main results were: (1) the eight teams, to a large extent, maintained a stable performance throughout the eight seasons analysed; (2) the length values decreased significantly from the fifth season (from 2015-2016 to 2018-2019); (3) the GkDef values decreased significantly from the fourth season (from 2014-2015 to 2018-2019); and 4) the TD values decreased significantly from the third season (from 2013-2014 to 2018-2019). The study concludes that within the framework of a performance stability, the teams over the seasons increased the density of players (e.g. less effective playing space), playing with the goalkeeper closer to the nearest defender of his team and covering less total distance.